Implementasi Mazhab dan Sistem Bermazhab dalam Kehidupan Komunitas Nahdlatul Ulama Sebagai Penguatan Pendidikan Islam - Sofiyulloh (Tarbawi : Jurnal Studi Pendidikan Islami, 2022)
A school of thought is a certain view related to religious law which is believed to be the truth because it is obtained using the ijma or qiyas method. The school of thought has become a system and has even become a lifestyle inherent in the Nahdliyin of the Nahdlatul Ulama community. This paper is a qualitative-descriptive research with a historical approach. The data collection technique uses a literature review that is relevant to the research topic. Data analysis using a thematic approach. The results of the research show that the Nahdliyin Nahdlatul Ulama have implemented 4 schools of thought (Syafi'i, Hanafi, Maliki, Hanbali) in their lives, because the Ulama figures who founded these schools believed that these 4 schools of thought had historical closeness to the Prophet Muhammad. This means that the 4 schools of thought are in accordance with the Al-Qur'an and Hadith.